Board Structure and Performance of Government-Linked and Non-Government-Linked Companies: A Comparative Study of Selected Listed Companies' in Malaysia, India and Singapore - Obeid, Amna; Sundarasen, Sheela Devi (International Journal of Economics and Financial Issues, 2017)
This study examines the relationship between board structure (proxied by non-executive directors, CEO duality, board size and independent directors) and company performance from the perspectives of profitability, liquidity and gearing amongst selected listed companies in Malaysia, India and Singapore. The study also determines the extent of similarities and divergences in the abovementioned relationships amongst the three countries. The results indicate that both Malaysia and India share similarities in most relationships but the reverse is documented for Singapore. It is conjectured that mere existence of governance may not be sufficient but its proper execution needs to be seriously considered by policy makers. This will ensure enhanced company performance and long-term survival and sustainability of companies. Keywords: Board structure, governance, performance, GLCs, non-GLCs, Malaysia, India and Singapore. JEL Classifications: G3, G34